Do Islamic banks have greater market power? - Laurent Weill (Bank of Finland, Institute for Economies in Transition (BOFIT), 2010)
The aim of this paper is to investigate whether Islamic banks have greater market power than con-ventional banks. An Islamic bank, for example, might enjoy enhanced market power if a captive clientele adhering to religious principles permits it to charge higher prices. To measure market power, we compute Lerner indices for a sample of banks from 17 countries where Islamic and conventional banks coexist. Comparison of Lerner indices shows no significant difference between Islamic banks and conventional banks over the period 2000-2007. When including control variables, regression of Lerner indices even suggests that Islamic banks have less market power than conventional banks. A robustness check with the Rosse-Panzar model confirms that Islamic banks are no less competitive than conventional banks. Thus, any reduced market power of Islamic banks can be attributed to differences in norms and incentives.
URN:NBN:fi:bof-201408071980
Keywords: 330